Can HRM lead to occupational integration? Evidence from Madagascar - Ravoaja, Hajaina (International Journal of Economics, Business, and Entrepreneurship, 2023)
In Madagascar, the number of underemployed has further outpaced the number of unemployed because of the gobal pandemic that has slowed down the economy. The concept of occupational or professional or vocational integration becomes more relevant in this context. While it was defined as access to the first job, it has been broadened towards the achievement of a stabilised position in the employment system. The aim of this study is to find out how Human Resources Management (HRM) can support the occupational integration of employees. The survey covered 222 young university graduates and 182 organisations that employed them. Cox regression was used to test the model for the influence of HRM modes and employment negotiation terms on the professional integration of young graduates. We found out that only the effect of the terms of employment negotiation by these graduates on his occupational integration is significant. The latter is important since continuity of operations depends on employees wanting to stay indefinitely.